Situating Students' Achievement and Perceptions of Inquiry-Oriented Instruction within Their Motivational Beliefs: A Mixed Methods Study. (3rd April 2021) - Zwanch, Karen; Mullins, Brooke; Fortune, Nicholas; Keene, Karen
ABSTRACT: Students' perceptions of the mathematics classroom environment have been linked to both cognitive and affective outcomes, as has inquiry-oriented instruction (IOI). The purpose of this mixed methods study is to determine what undergraduate students' perceptions of inquiry-oriented differential equations are, and the extent to which their perceptions are related to their academic achievement. The results are framed using motivational theory. Results are that students' perceptions of IOI fit within four themes: Engaging with Math and Each Other, Less to Know, Feelings of Frustration, and Resistance to IOI. Furthermore, a linear mixed model indicated that students with positive and neutral perceptions of IOI are predicted to score approximately 10% higher on the end of course assessment than are their peers with negative perceptions of IOI. Qualitative and quantitative results are linked by expectancy-value theory, which leads to the conclusion that students who perceive of IOI as useful to their learning and who perceive that they can be successful in IOI have significantly higher achievement in an undergraduate mathematics course.